2017
DOI: 10.18632/oncotarget.21422
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative and apoptotic effects of xanthohumol in cholangiocarcinoma

Abstract: Cholangiocarcinoma remains the second most prevalent hepatic neoplasm in the United States with a 5-year survival rate of less than 10%. Currently, no systemic therapy has demonstrated efficacy. Therefore, an urgent need for the identification of molecularly targeted compound(s) remains. The Notch signaling pathway has been shown to be dysregulated in cholangiocarcinoma, exhibiting hyperactivity while also possibly mediating chemotherapeutic resistance. We analyzed the effects of xanthohumol, a prenylated chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…Control wells were treated with DMSO. All wells were made in quadruplicate, and all plates were incubated for 48, 72, or 96 h. Cell viability was measured as described [ 25 , 26 ]. The assay was repeated at least three times.…”
Section: Methodsmentioning
confidence: 99%
“…Control wells were treated with DMSO. All wells were made in quadruplicate, and all plates were incubated for 48, 72, or 96 h. Cell viability was measured as described [ 25 , 26 ]. The assay was repeated at least three times.…”
Section: Methodsmentioning
confidence: 99%
“…Silencing of MLK3 significantly reduces the expression of apoptotic associated proteins such as cleaved caspase‐3, cleaved PARP, Bad and Bax, as well as increasing the expression of Bcl‐2 and ratio of Bcl‐2/Bax in cardiomyocytes . Notch‐1 signalling participates in tumourigenesis, chemoresistance, cancer cell growth, and metastasis . It is elevated in organ‐specific cancers, including gynaecological malignancies .…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Notch-1 signalling participates in tumourigenesis, chemoresistance, cancer cell growth, and metastasis. 25 It is elevated in organ-specific cancers, including gynaecological malignancies. 26,27 Accumulating data has suggested that Notch-1 is implicated in autophagy and plays a critical role in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed that 1 has also the ability to sensitize MCF-7/ADR cells to doxorubicin, which increases cytotoxic effect of this chemotherapy drug (Liu et al, 2017). The mechanism of anticancer activity of xanthohumol described most often involves its ability to suppress cell proliferation and induce programmed cell death in cancerous cells (Min et al, 2017;Walden et al, 2017). Xanthohumol (1) and its structural analogues are also inhibitors of many enzymes, such as cyclooxygenase and lipoxygenase, which can be involved in formation of reactive oxygen species.…”
Section: Introductionmentioning
confidence: 99%